Tp-e/QTc ratio as a potential non-invasive marker of coronary lesion severity assessed by SYNTAX score in non-ST segment elevation myocardial infarction - Ginting, Yehezkiel Bastanta; Sitepu, Andika; Ketaren, Andre Pasha; Hasan, Harris; Lubis, Anggia Chairuddin; Haykal, Teuku Bob; Ginting, Daniel (Heart Science Journal, 2026)
Background: Accurate assessment of coronary lesion burden in the initial stage is the basis for appropriate therapy in NSTEMI patients. As a parameter derived from the ECG that reflects ventricular repolarization variability, the Tp-e/QTc ratio is suggested as a noninvasive predictor for assessing anatomical complexity. Objective: Investigating the relationship of Tp-e/QTc with the severity of coronary lesions on angiography assessed using the SYNTAX score, in patients with NSTEMI. Methods: Utilized a retrospective cohort approach with a cross-sectional design. In total, 141 patients were selected by utilizing purposive sampling. The Tp-e and QTc intervals were manually measured from 12-lead ECGs using the tangent method, and the Tp-e/QTc ratio was calculated. SYNTAX scores were independently determined by two interventional cardiologists. Data were analyzed using bivariate and multivariate analyses. Result: Higher SYNTAX group (0.26 ± 0.047) had higher Tp-e/QTc than lower SYNTAX group (0.21 ± 0.052). Tp-e/QTc showed a positive correlation with SYNTAX score (r = 0.395; p < 0.001) and remained an independent predictor (β = 0.332; p = 0.001). The ROC curve displayed strong discrimination (AUC = 0.817), a cut-off of 0.24 yielded 82.7% sensitivity and 76.4% specificity. Conclusion: Tp-e/QTc is associated with angiographic complexity in NSTEMI and may support early risk stratification prior to angiography.